2021
DOI: 10.3389/fpsyg.2021.562800
|View full text |Cite
|
Sign up to set email alerts
|

Social, Family, and Educational Impacts on Anxiety and Cognitive Empathy Derived From the COVID-19: Study on Families With Children

Abstract: This research aims to monitor the current situation of confinement in Spanish society motivated by COVID-19 crisis. For this, a study of its socio-family, psychological and educational impact is conducted. The sample (N = 165 families, 89.1% nuclear families with children living in the same household and 20.5% with a relative in a risk group) comes from the Aragonese region (Spain). The instruments used are: Beck-II Depression Inventory (BDI-II); Baron-Cohen and Wheelwright’s Empathy Quotient (EQ) with its cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 54 publications
1
3
0
5
Order By: Relevance
“…These results are consistent with those of Deirdre et al, who showed that many parents had to juggle work commitments with the increased demands on their time, including the practical aspects of supervising children's learning, exercise and play [19]. A study of the general Spanish population during the COVID-19 pandemic showed that anxiety was positively associated with the female gender and with the time spent helping their children, as in our study [20]. Our study also found that anxiety was associated with annoyance by noise, as highlighted in the study by Amerio et al [21].…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with those of Deirdre et al, who showed that many parents had to juggle work commitments with the increased demands on their time, including the practical aspects of supervising children's learning, exercise and play [19]. A study of the general Spanish population during the COVID-19 pandemic showed that anxiety was positively associated with the female gender and with the time spent helping their children, as in our study [20]. Our study also found that anxiety was associated with annoyance by noise, as highlighted in the study by Amerio et al [21].…”
Section: Discussionsupporting
confidence: 93%
“…We observed that, about one year after the global pandemic outbreak, empathic social skills were impacted negatively whereas perspective-taking and emotional empathy increased. The capacity to empathize with and share another’s emotion could represent a person’s strength, while reduced empathic social skills could be a weakness to be targeted in psychological interventions to help people cope with the mental health challenges related to COVID-19 pandemic [ 3 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…La literatura académica expone la innegable comorbilidad que tiene la adicción a Internet con otras patologías como depresión, ansiedad, trastornos internalizantes y externalizantes, insomnio, traumas infantiles, etc. (Brailovskaia et al, 2019;Quílez-Robres et al, 2021;Lozano et al, 2020;Lu et al, 2018;Tas, 2019). De manera específica, las personas que padecen adicción a Internet y ansiedad exponen cómo las redes sociales retroalimentan la sintomatología ansiosa.…”
Section: Marco Teóricounclassified
“…De inicio, los resultados son coincidentes con investigaciones previas que señalan el aumento de la prevalencia de esta patología (Černja et al, 2019;Cheng y Li, 2014;Müller et al, 2014). Una de las mayores dificultades a las que se enfrenta el sistema sanitario y educativo es la comorbilidad elevada de la adicción junto a trastornos como la ansiedad, y a dificultades en habilidades sociales y empatía (Brailovskaia et al, 2019;Quílez-Robres et al, 2021;Lozano et al, 2020;Lu et al, 2018;Tas, 2019).…”
Section: Discusión Y Conclusionesunclassified
See 1 more Smart Citation